Collective Impact in/for Adult Education: A Framework for Collective Action to Address Community Complexity and Resilience - Kim L. Niewolny; Thomas G. Archibald (Adult Education Research Conference, 2015)
We explore how adult educators may (re)position their praxis to focus on the social action goals of adult education by envisioning the possibilities of Collective Impact (CI) and evaluation capacity building. Implications emphasize the potential of achieving collective impact outcomes to address community complexity, resiliency, and systems-level change.
Keywords: collective impact; social action; evaluation capacity building